Sanctions and the Exchange Rate - Itskhoki, Oleg; Mukhin, Dmitry (Review of Economic Studies, 2026)
Abstract Trade wars and financial sanctions are again becoming an increasingly common part of the international economic landscape, and the dynamics of the exchange rate are often used in real time to evaluate the effectiveness of sanctions and policy responses. We show that sanctions limiting a country’s exports or freezing its assets depreciate the exchange rate, while sanctions limiting imports appreciate it, even when both types of policies have exactly the same effect on real allocations, including household welfare and government fiscal revenues. Beyond the direct effect from sanctions, increased precautionary savings in foreign currency also depreciate the exchange rate when they are not offset by the sale of official reserves or financial repression of foreign-currency savings. We show that the dynamics of the ruble exchange rate following Russia’s invasion of Ukraine in February 2022 are quantitatively consistent with the combined effects of these forces calibrated to the observed sanctions and government policies. We evaluate the associated welfare, fiscal and inflationary consequences for both Russia and the coalition of Western countries.